2017
DOI: 10.2495/tdi-v2-n1-39-48
|View full text |Cite
|
Sign up to set email alerts
|

Do policy measures in fact promote electric mobility? A study across 20 countries

Abstract: In a 2015 study, policy measures to promote electric mobility were examined with regard to their acceptance by consumers in 20 countries on five continents. results of a choice-based conjoint analysis showed that people appreciate monetary incentives; however, the application of the Kano method to detect dissatisfaction with missing features revealed that charging networks are absolute must-haves. In the same 20 countries, the present article examines the actual effects of three kinds of policy measures: monet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Adequate infrastructure may be absent, speed a part of modern life Monetary incentives and traffic regulations favouring electric vehicles; investment in public charging infrastructure; car purchase tax calculated by a combination of weight, CO 2 and NO x emissions(Haugneland and Kvisle 2015;Globisch et al 2018;Gnann et al 2018;Lieven and Rietmann 2018;Rietmann and Lieven 2019) …”
mentioning
confidence: 99%
“…Adequate infrastructure may be absent, speed a part of modern life Monetary incentives and traffic regulations favouring electric vehicles; investment in public charging infrastructure; car purchase tax calculated by a combination of weight, CO 2 and NO x emissions(Haugneland and Kvisle 2015;Globisch et al 2018;Gnann et al 2018;Lieven and Rietmann 2018;Rietmann and Lieven 2019) …”
mentioning
confidence: 99%
“…Incentive strategies and subsidies for an increasing EV fleet: The adoption of measures, either financial incentives for EV purchase [52] or non-financial traffic incentives for EVs [53], or tax exemptions and subsidies for charging infrastructure [48], all play a positive effect on the promotion of e-mobility, especially at the early stage of the market, when the economic viability of investments in charging infrastructure is uncertain.…”
mentioning
confidence: 99%
“…In a review of 50 case studies throughout developed countries, Negro et al (2012) indicate the necessity of stable long term, but flexible, incentives.Governmental policy is regarded as essential for the successful diffusion of vehicle technologies, regardless of a country's development level Jenn et al (2018). concluded that in the US, for each $1000 incentive, electric vehicle sales rise by 2.6% Lieven and Rietmann (2018). found that the number of charging stations magnifies the effect of monetary incentives on the diffusion of electric vehicles.…”
mentioning
confidence: 99%